SiO2-TiO2 Films Supported on Ignimbrite by Spray Coating for the Photocatalytic Degradation of NOx Gas and Methyl Orange Dye - Gallegos Florez, Daily Maria Magdalena (2020)
In this work, a SiO2-TiO2 coating, composed of different numbers of TiO2 and SiO2 layers, was fabricated by a spray-coating technique. The films were deposited onto ignimbrite rock and divided into two groups according to the number of SiO2 layers applied, 10 and 15 layers of SiO2 and 5 layers of TiO2 for each group. The morphology and chemical composition of the synthesized samples were characterized by field emission scanning electron microscopy (FE-SEM) and energy dispersive X-ray spectrometer (EDS), which reveal the successful SiO2-TiO2 coating on ignimbrite. The photocatalytic activities of samples obtained were evaluated toward the decomposition of 3 ppm of methyl orange (MO). Finally, NOx gas degradation was studied. The obtained results evidenced that the SiO2 and TiO2 coating improved the photocatalytic activity of ignimbrite.